EVALUASI KELAYAKAN TEKNIS LALU LINTAS PADA PERANCANGAN UNDERPASS JATINGALEH SEMARANG - Cahyono, Budi Agus; Arwani, Yunus; Supriyono, Supriyono; Yulipriyono, Epf. Eko (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2014)
Semarang Jatingaleh region is one of the areas through which the access point to the southern region of Semarang, it’s at Teuku Umar’s steet and Setiabudi’s street. The road that connects the city to Banyumanik Semarang and Central Java Tembalang and southern regions. Jatingaleh region including areas very dense traffic flow coupled with the growth of vehicles each year. At rush hour in the Jatingaleh always a jam at some point intersection. To overcome this, the government has made a solution, namely the planned construction of the underpass. Based on the description above, there should be an evaluation of the technical feasibility of the results of the design traffic underpass Jatingaleh Semarang. The data collection method used was a survey of traffic volume and the side barriers. Secondary data such as drawing DED (Detail Engineering Design) underpass Jatingaleh Semarang such as traffic flow layout, road cross section, and looked over the underpass. The method of analysis consisted of road performance, the performance of intersection, part single braid, and geometric u -turn. The results showed the degree of saturation (DS) is the largest road performance 1.18 at Teuku Umar’s street segment 2 way to the city. Greatest value of the degree of saturation (DS) method was signalized intersections is 0.52 with a biggest value of intersection delay (D) is 8.84 second /smp whereas intersection method the degree of saturation (DS) is 0.55 with the largest intersection delay value (D) the largest is 9.27 sec/sm, intersection Kaliwiru that can not operate optimally it can be seen from the value of the degree of saturation (DS) at the intersection of Teuku Umar street is 0.91 and at Sultan Agung street is 0.87 with delay(D) is 16,58 second/smp then the largest queue length reaches 251.4 meters on Teuku Umar street.. Greatest value of the degree of saturation (DS) is a single braid section 0.88 on Setiabudi street to Teuku Umar street. Geometric u-turn is in compliance with applicable regulatory standards.